Case Report: Acute primary splenic torsion in a maned wolf (Chrysocyon brachyurus) - Hernandez, Geovanna; Picavet, Pierre P.; Bruwier, Aurelie; Soula, Mariajesus; Tovar-Lopez, Gretel (Frontiers in Veterinary Science, 2025)
Splenic torsion is an uncommon condition in the Canidae family, characterized by twisting of the splenic pedicle, leading to vascular compromise. The etiology remains unclear, although one hypothesis associates it with gastric dilatation-volvulus syndrome. Splenic torsion may present acutely or chronically. Tentative diagnosis is often based on clinical signs, physical examination findings, and abdominal radiography, while ultrasonography or computed tomography confirms the condition. A 6-year-old castrated male maned wolf (Chrysocyon brachyurus) was presented to the Veterinary Health Center at Kansas State University with an acute onset of anorexia, lethargy, and apparent ataxia. Physical examination revealed pale, moist mucous membranes, a firm and large mass occupying most of the cranial abdomen, and suspected abdominal effusion. Abdominal ultrasound and computed tomography confirmed an acute splenic torsion. Emergency splenectomy was performed, and diagnosis was confirmed grossly and subsequently by histopathologic study. The patient received a xenotransfusion with one unit of canine packed red blood cells and two units of canine plasma intraoperatively. Recovery was uneventful, and no complications were noted 7 months postoperatively. This case report documents the first recorded instance of acute primary splenic torsion in a maned wolf. Diagnostic imaging findings were comparable to those seen in domestic dogs, and similar therapeutic approach resulted in a successful outcome.